Digital Gastronomy Tourism Influence Based on Clay Video Consumption Interest in Traditional Batak Toba Lapet Food - Madeline Cia; Yudhiet Fajar Dewantara (Darul Yasin Al Sys, 2026)
Traditional Indonesian food, particularly Lapet Batak Toba, is experiencing a decline in consumption interest among younger generations due to the dominance of fast food and the accelerating influence of globalization. At the same time, more than 82% of Generation Z and millennials use social media as their primary source of culinary inspiration, creating strategic opportunities to digitalize traditional cuisine through creative content. This study aims to analyze the influence of Digital Gastronomy Tourism Influence (DGTI) based on clay video on consumption interest in Lapet Batak Toba among Generation Z and millennials, using the Stimulus–Organism–Response (S–O–R) framework. An explanatory quantitative approach was employed through a survey of 100 respondents aged 18–45 years who were active users of short-video platforms, including TikTok, Instagram Reels, and YouTube Shorts, in Jakarta, Medan, and surrounding areas of North Sumatra. Respondents were selected using purposive sampling, and the data were analyzed using simple linear regression with IBM SPSS Statistics 29. The findings indicate that clay video-based DGTI has a positive and significant influence on consumption interest in Lapet Batak Toba, with an R² value of 0.593, indicating that the model explains 59.3% of the variation in consumption interest. Descriptive analysis by dimension shows that digital marketing, consumer motivation, and consumer behavior contribute most dominantly to the formation of consumption interest, whereas the digital platform dimension functions as a supporting element within the content distribution ecosystem. This study concludes that clay video content is an effective promotional medium for traditional cuisine within the digital gastronomy framework. The findings contribute to the literature on digital gastronomy tourism and provide practical implications for culinary SMEs, content creators, and government stakeholders in optimizing culturally oriented digital marketing strategies for Indonesian culinary heritage preservation.